Drug-excipient interaction and its importance in dosage form development - Nishath Fathima, Tirunagari Mamatha, Husna Kanwal Qureshi, Nandagopal Anitha, Jangala Venkateswara Rao (Journal of Applied Pharmaceutical Science)
Excipients are included in dosage forms to aid manufacture, administration or absorption. Although considered pharmacologically inert, excipients can initiate, propagate or participate in chemical or physical interactions with drug compounds, which may compromise the effectiveness of a medication. Exicipients are not exquisitely pure. Even for the most commonly used excipients, it is necessary to understand the context of their manufacture in order to identify potential active pharmaceutical ingredients interactions with trace components. Chemical interactions can lead to degradation of the active ingredient, thereby reducing the amount available for therapeutic effect. Physical interactions can affect rate of dissolution, uniformity of dose or ease of administration.
Keywords: Excipient, Drug, Interaction, Physical, Chemical.